Characterisation of antimicrobial usage in Danish pigs in 2020 - Moura, Pedro; Sandberg, Marianne; Høg, Birgitte Borck; Niza-Ribeiro, João; Nielsen, Elisabeth Okholm; Alban, Lis (Frontiers in Veterinary Science, 2023)
Introduction Denmark is one of the world’s largest exporters of pigs and pig meat, so the sector plays an important role in the national antimicrobial use (AMU). The Danish government has run antimicrobial stewardship programs in collaboration with the pig industry for more than 25 years. These have resulted in substantial overall reductions in total AMU and limiting the use of fluoroquinolones, the 3rd and 4th generation cephalosporines and the polymyxin colistin. To understand where further reductions in AMU could take place, it is necessary to investigate which antimicrobials are being used, how, and for which reasons. Materials and methods We characterized the AMU in the Danish pig sector in 2020, providing new analytical insights based on data retrieved from the VetStat database. The AMU data were segmented into classes, routes of administration, treatment indications and age groups, and interpreted as an outcome of the interventions taken. We evaluated the current AMU regarding choice of antimicrobial class. Moreover, we discussed how to further improve the antimicrobial stewardship in Danish pig production to achieve additional reductions without jeopardizing animal welfare. Where relevant, two pig veterinary specialists were consulted. Results In 2020, 43.3 mg antimicrobials per population correction unit (PCU) were ascribed to the Danish pig sector. There was practically no use of fluoroquinolones, 3rd and 4th generation cephalosporins and polymyxins. Weaners related to 45% of the total AMU in pigs when measured in tonnes and 81% when measured in defined animal daily doses, of these 76% were ascribed to gastrointestinal indications and overall, 83% were administered perorally. Conclusion To enable further reductions in AMU, it should be investigated how and when to replace group treatments (e.g., all animals in section or a pen) with individual treatments. Moreover, prevention of disease and promotion of animal health should be prioritized, e.g., through focus on feed, vaccination, biosecurity, and disease eradication.